Natural Processes and Human Impacts Interactions between Humanity and the Environment - Govorushko, Sergey M. (Springer Netherlands : Imprint: Springer, 2012)
This highly topical book comes at a time when the two-way relationship between humankind and the environment is moving inexorably to the top of the agenda. It covers both sides of this delicate balancing act, explaining how various natural processes influence humanity, including its economic activities and engineering structures, while also illuminating the ways in which human activity puts pressure on the natural environment. Chapters analyze a varied selection of phenomena that directly affect people's lives, from geological processes such as earthquakes and tsunamis to cosmic events such as magnetic storms. The author moves on to consider the effect we have on nature, ranging from the impact of heavy industry to the environmental consequences of sport and recreational pastimes. Complete with maps, photographs and detailed case studies, this book provides a comprehensive overview of the biggest issue we face as a species-the way we relate to the natural world around us. This book includes more than 100 maps showing the global distribution of different natural processes/human activities and more that 450 photographs from many countries and all oceans. It will provide a valuable resource for both graduate students and researchers in many fields of knowledge. Sergey Govorushko is a chief research scholar at the Pacific Geographical Institute, Russian Academy of Sciences. He is also Professor at the Far Eastern Federal University (Vladivostok). Sergey Govorushko received his PhD from the Institute of Geography, Russian Academy of Sciences. His research activities focus on the interaction between humanity and the environment, including the impact of nature on humanity; the impact of humanity on the environment; and assessment of the interaction (environmental impact assessment, environmental audit, etc.). He has authored eight and co-authored seven monographs.